The Influence of STAD Learning Model, Discussion and Learning Interest toward Learning Outcomes of Elementary School Students - sulami, Sulami; Karlina Marjo, Happy; Sardjiyo (Universitas Pancasakti Tegal, 2022)
This study aimed to determine the effect of the STAD type learning model, discussion and learning interest on social studies learning outcomes in elementary school. This type of research is an experimental study comparing student learning outcomes between the experimental and control classes. This study took place at SDN Kedoya Utara 01 Kebon Jeruk, West Jakarta. The population in this study were all fifth grade students at SDN Kedoya Utara 01 with 64 students. The sample in this study is not students as individuals but classes. The level sample was determined by purposive sampling for fifth grade students. The data were obtained through instrument and documentation questions. The data analysis techniques are r test analysis and t test. Based on the analysis, conclusions are obtained. There is a significant effect on the STAD type cooperative learning model, discussion and interest in learning together have an effect on learning outcomes for social studies subjects with Fcount = 23,444% Sig = 0.0000 <0.05. Then there is a significant effect on the STAD type of cooperative learning model that affects the learning outcomes of social studies subjects with t = 5.961% and Sig = 0.0000 <0.05. Furthermore, there is an insignificant effect on the perception of the Discussion-type cooperative learning model and interest in learning together to influence the learning outcomes of social studies subjects with Fcount = 3.444% Sig = 0.0000 <0.05. 4. So that it can be concluded that there is a simultaneous influence between the STAD cooperative learning model, discussion with learning interest on social studies learning outcomes.